CFD investigation into resistance characteristics of a pusher-barge system in calm water - Fitriadhy, Ahmad -; Adam, Nur Amira; Pison, Izzati; A. Rahman, Mohd Asamudin; Musa, Mohd Azlan; Mohd, Mohd Hairil (Journal of Naval Architecture and Marine Engineering, 2021)
Prediction of ship’s total resistance of a pusher-barge system has become enormous complexity involving nonlinear-hydrodynamic flows behaviour along their hull forms. Both of empirical and simplified numerical solutions may still lead into inaccurate results due to presence of nonlinear characteristics of the pressure and viscous resistances. The use of a more sophisticated method would obviously necessitate to solve the above problem. This paper presents a Computational Fluid Dynamics (CFD) approach to predict the total ship’s resistance of a pusher-barge system at various barge’s configurations. To achieve such objective, four different configurations of the barge models incorporated with various Froude numbers have been taken into account in the computational simulation. In general, the results revealed that the increase of Froude number (Fr = 0.182 to 0.312) was proportional to the magnitude of RT, RP and RV. Regardless of the various Froude number, the pusher-barge system with a 13BP configuration provides the highest resistance compared to the 12BP and 11BP. In addition, the arrangement of barges in the longitudinal (12BP) and lateral (21BP) configurations produced a significant effect with increases in RT, RP and RV values of 110%, 167.5% and 77.6%, respectively. The possible reason for this is that the increase of the total wetted surface area for 21BP has produced to a proportionally higher amount of the pressure and viscous resistance. Overall study, the numerical results were presented and analysed based on few aspects involved the total resistance and resistance coefficient in terms of pressure and viscous resistance of the pusher-barge system. This analysis provides very valuable information on choosing the most reliable arrangement of pusher-barge system. This analysis provides very valuable information on choosing the most reliable arrangement of pusher-barge system